2014
DOI: 10.1021/ml500297n
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Studies Reveal the Oxazinone Ring Is a Determinant of Cytochrome P450 2B6 Activity Toward Efavirenz

Abstract: Cytochrome P450 2B6 (CYP2B6) is primarily responsible for the metabolism of the anti-HIV drug efavirenz (EFV). We set out to explore the molecular basis for CYP2B6 activity toward EFV by examining the metabolism of eight EFV analogues. cDNA-expressed CYP2B6 formed monooxygenated metabolites from EFV analogues containing an intact oxazinone or oxazine ring, but not from analogues with a disrupted ring, suggesting this ring is important for metabolism of EFV by CYP2B6. Subsequent substrate depletion analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 21 publications
5
23
0
Order By: Relevance
“…We previously showed that elimination of this position altogether, resulted in a lower K M and higher V max compared to EFV. [13] Our data obtained here demonstrate that addition of a hydrophobic methyl group also results in tighter binding, as is suggested by the lower K M value. Thus, our work here further supports that the presence of a carbonyl oxygen atom seems to decrease the affinity of CYP2B6 for EFV.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…We previously showed that elimination of this position altogether, resulted in a lower K M and higher V max compared to EFV. [13] Our data obtained here demonstrate that addition of a hydrophobic methyl group also results in tighter binding, as is suggested by the lower K M value. Thus, our work here further supports that the presence of a carbonyl oxygen atom seems to decrease the affinity of CYP2B6 for EFV.…”
Section: Discussionsupporting
confidence: 71%
“…We then incubated CYP2B1 with each of the eight EFV analogues reported previously. [13] We again found that CYP2B1 mirrored CYP2B6 activity towards our entire panel of EFV analogues, including M2 formation from E-dihydroefavirenz, M4 and M5 formation from the pentynyl analogue, and M2 formation from the oxazine analogue. Moreover, with the exception of 2 -M2, 3 -M1, 4 -M2, and 5 -M1; metabolite formation from our panel of EFV analogues differed by less than 3-fold between CYP2B6 and CYP2B1 (Figure 5).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations